Metformin's effects on varicocele, erectile dysfunction, infertility and prostate-related diseases: A retrospective cohort study - Chin-Hsiao Tseng; Chin-Hsiao Tseng; Chin-Hsiao Tseng (Frontiers Media S.A., 2022)
Objectives: To investigate the risk of varicocele, erectile dysfunction (ED), infertility, prostatitis, benign prostate hyperplasia (BPH) and prostate cancer associated with metformin use.Materials and methods: A total of 261,838 males, mean age 52.39 years (SD: 11.39), with a new-onset type 2 diabetes mellitus in 1999-2009 were identified from Taiwan's National Health Insurance. Among them, 175,171 were metformin initiators [metformin (+)] and 86,667 were non-metformin initiators [metformin (−)] in the initial 12-month prescriptions of antidiabetic drugs. Follow-up started after the initial 12-month prescriptions. Outcomes were followed up until 31 December 2011. Intention-to-treat (ITT) and per-protocol (PP) hazard ratios comparing metformin (+) to metformin (−) were estimated by Cox regression incorporated with the inverse probability of treatment-weighting using propensity scores.Results: The median follow-up time ranged 5.55-6.82 years in metformin (−) and 4.36-5.17 years in metformin (+) for different outcomes in ITT analyses. The respective median follow-up time in PP analyses ranged 2.20-2.61 years in metformin (−) and ranged 3.99-4.65 years in metformin (+). In the ITT analyses, for metformin (−), the incidence rates (per 100,000 person-years) of varicocele, ED, infertility, prostatitis, BPH and prostate cancer were 26.42, 455.89, 22.82, 590.23, 4226.19, and 141.69, respectively; and the respective incidence rates for metformin (+) were 25.65, 488.10, 32.60, 510.30, 3685.66, and 116.57. The hazard ratios (95% confidence intervals) comparing metformin (+) to metformin (−) in the ITT analyses were 0.960 (0.784-1.174) for varicocele, 1.077 (1.026-1.130) for ED, 1.368 (1.116-1.676) for infertility, 0.887 (0.849-0.927) for prostatitis, 0.883 (0.868-0.899) for BPH and 0.878 (0.802-0.961) for prostate cancer. The hazard ratios for the respective outcomes in the PP analyses were 0.845 (0.662-1.078), 1.350 (1.264-1.441), 1.396 (1.078-1.808), 0.800 (0.756-0.846), 0.875 (0.855-0.895), and 0.613 (0.548-0.686).Conclusion: Metformin use in patients with type 2 diabetes mellitus is associated with a neutral effect on varicocele, a higher risk of sexual dysfunction (ED and infertility) and a reduced risk of prostate-related health (prostatitis, BPH and prostate cancer).